# Iterative algorithms based on hybrid method and Cesàro mean of asymptotically nonexpansive mappings for equilibrium problems

• 767 Accesses

• 1 Citations

## Abstract

Using Cesàro means of a mapping, we modify the progress of Mann’s iteration in hybrid method for asymptotically nonexpansive mappings in Hilbert spaces. Under suitable conditions, we prove that the iterative sequence converges strongly to a fixed point of an asymptotically nonexpansive mapping. We also introduce a new hybrid iterative scheme for finding a common element of the set of common fixed points of asymptotically nonexpansive mappings and the set of solutions of an equilibrium problem in Hilbert spaces.

MSC:47H10, 47J25, 90C33.

## 1 Introduction

Let H be a real Hilbert space with the inner product $〈⋅,⋅〉$ and the norm $∥⋅∥$. Let C be a nonempty closed convex subset of H. A mapping $T:C→C$ is said to be asymptotically nonexpansive if for each $n≥1$, there exists a nonnegative real number $k n$ satisfying $lim n → ∞ k n =1$ such that

$∥ T n x − T n y ∥ ≤ k n ∥x−y∥,∀x,y∈C;$

when $k n ≡1$, T is called nonexpansive.

The concept of asymptotically nonexpansive mapping was introduced by Goebel and Kirk  in 1972. We denote by $F(T):={x∈C:Tx=x}$ the set of fixed points of T. It is well known that if $T:H→H$ is asymptotically nonexpansive, then $F(T)$ is nonempty convex.

In 1953, Mann  introduced the iteration as follows: a sequence ${ x n }$ defined by

$x n + 1 = α n x n +(1− α n )T x n .$
(1.1)

In an infinite-dimensional Hilbert space, Mann iteration could conclude only weak convergence . Attempts to modify the Mann iteration method (1.1) so that strong convergence is guaranteed have recently been made. Nakajo and Takahashi  proposed the following modification of Mann iteration method for a nonexpansive mapping T in a Hilbert space:

${ x 0 ∈ C is arbitrary , y n = α n x n + ( 1 − α n ) T x n , C n = { z ∈ C : ∥ y n − z ∥ ≤ ∥ x n − z ∥ } , Q n = { z ∈ C : 〈 x n − z , x 0 − x n 〉 ≥ 0 } , x n + 1 = P C n ∩ Q n ( x 0 ) , n = 0 , 1 , 2 … ,$
(1.2)

where $P K$ denotes the metric projection from H onto a closed convex subset K of H. The above method is also called CQ method or hybrid method.

In 2006, Kim and Xu  adapted the iteration (1.2) in a Hilbert space. More precisely, they introduced the following iteration process for asymptotically nonexpansive mappings:

${ x 0 ∈ C is arbitrary, y n = α n x n + ( 1 − α n ) T n x n , C n = { z ∈ C : ∥ y n − z ∥ 2 ≤ ∥ x n − z ∥ 2 + θ n } , Q n = { z ∈ C : 〈 x n − z , x 0 − x n 〉 ≥ 0 } , x n + 1 = P C n ∩ Q n ( x 0 ) , n = 0 , 1 , 2 … ,$
(1.3)

where

They proved that ${ x n }$ converges in norm to $P F ( T ) x 0$ under some conditions. Several authors (see [6, 7]) have studied the convergence of hybrid method.

Baillon  first proved that the following Cesàro mean iterative sequence weakly converges to a fixed point of a nonexpansive mapping in Hilbert spaces:

$T n x= 1 n + 1 ∑ i = 0 n T i x.$

Shimizu and Takahashi  proved a strong convergence theorem of the above iteration for an asymptotically nonexpansive mapping in Hilbert spaces.

Let C be a nonempty closed convex subset of a real Hilbert space H, let $f:C×C→R$ be a functional, where is the set of real numbers. The equilibrium problem is to find $x ˆ ∈C$ such that

$f(x,y)≥0,∀y∈C.$
(1.4)

The set of solutions of (1.4) is denoted by $EP(f)$. Given a mapping $T:C→ X ∗$, let $f(x,y)=〈Tx,y−x〉$, $∀x,y∈C$, then $z∈EP(f)$ if and only if $〈Tz,y−z〉≥0$, $∀y∈C$, i.e., z is the solution of the variational inequality.

There are several other problems, for example, the complementarity problem, fixed point problem and optimization problem, which can also be written in the form of an equilibrium problem. So, equilibrium problems provide us with a systematic framework to study a wide class of problems arising in financial economics, optimization and operation research etc., which motivates the extensive concern. See, for example, . In recent years, equilibrium problems have been deeply and thoroughly researched. See, for example, . Some methods have been proposed to solve the equilibrium problem in a Hilbert space; see, for instance, . In 2011, Jitpeera, Katchang, and Kumam  found a common element of the set of solutions for mixed equilibrium problem, the set of solutions of the variational inequality for a β-inverse strongly monotone mapping, and the set of fixed points of a family of finitely nonexpansive mappings in a real Hilbert space by using the viscosity and Cesàro mean approximation method.

Motivated by the above-mentioned results, in this paper we introduce the following iteration process for asymptotically nonexpansive mappings T with C a closed convex bounded subset of a real Hilbert space:

${ x 0 ∈ C is arbitrary, y n = α n x n + ( 1 − α n ) 1 n + 1 ∑ j = 0 n T j x n , C n = { z ∈ C : ∥ y n − z ∥ 2 ≤ ∥ x n − z ∥ 2 + θ n } , Q n = { z ∈ C : 〈 x n − z , x 0 − x n 〉 ≥ 0 } , x n + 1 = P C n ∩ Q n ( x 0 ) , n = 0 , 1 , 2 … ,$
(1.5)

where

We shall prove that the above iterative sequence ${ x n }$ converges strongly to a fixed point of T under some proper conditions. In addition, we also introduce a new hybrid iterative scheme for finding a common element of the set of common fixed points of asymptotically nonexpansive mappings and the set of solutions of an equilibrium problem in Hilbert spaces.

We will use the notation for weak convergence and → for strong convergence.

## 2 Preliminaries

Let H be a real Hilbert space. Then

$∥ x − y ∥ 2 = ∥ x ∥ 2 − ∥ y ∥ 2 −2〈x−y,y〉$
(2.1)

and

$∥ λ x + ( 1 − λ ) y ∥ 2 =λ ∥ x ∥ 2 +(1−λ) ∥ y ∥ 2 −λ(1−λ) ∥ x − y ∥ 2$
(2.2)

for all $x,y∈H$ and $λ∈[0,1]$. It is also known that H satisfies

1. (1)

Opial’s condition, that is, for any sequence ${ x n }$ with $x n ⇀x$, the inequality

$lim inf n → ∞ ∥ x n −x∥< lim inf n → ∞ ∥ x n −y∥$

holds for every $y∈H$ with $y≠x$.

2. (2)

The Kadec-Klee property, that is, for any sequence ${ x n }$ with $x n ⇀x$ and $∥ x n ∥→∥x∥$ together implies $∥ x n −x∥→0$.

Let C be a nonempty closed convex subset of H. Then, for any $x∈H$, there exists a unique nearest point in C, denoted by $P C (x)$, such that

$∥ x − P C ( x ) ∥ ≤∥x−y∥,∀y∈C.$

Such a mapping $P C$ is called the metric projection of H onto C. We know that $P C$ is nonexpansive. Furthermore, for $x∈H$ and $z∈C$,

$z= P C (x)if and only if〈x−z,z−y〉≥0,∀y∈C.$

We also need the following lemmas.

Lemma 2.1 (See )

Let T be an asymptotically nonexpansive mapping defined on a bounded closed convex subset C of a Hilbert space H. Assume that ${ x n }$ is a sequence in C with the properties: (i) $x n ⇀z$; (ii) $T x n − x n →0$. Then $z∈F(T)$.

Lemma 2.2 (See )

Let C be a nonempty bounded subset of a Hilbert space. Let T be an asymptotically nonexpansive mapping from C into itself such that $F(T)$ is nonempty. Then, for any $ε>0$, there exists a positive integer $l ε$ such that for any integer $l≥ l ε$, there is a positive integer $n l$ satisfying

$∥ 1 n + 1 ∑ j = 0 n T j x − T l ( 1 n + 1 ∑ j = 0 n T j x ) ∥ <ε,∀x∈C,∀n≥ n l .$

The equilibrium problem is to find $x ˆ ∈C$ such that

$f( x ˆ ,y)≥0,∀y∈C.$

The set of solutions of the above inequality is denoted by $EP(f)$. For solving the equilibrium problem, let us assume that a bifunction f satisfies the following conditions:

(A1) $f(x,x)=0$ for all $x∈C$;

(A2) f is monotone, i.e., $f(x,y)+f(y,x)≤0$, for all $x,y∈C$;

(A3) for each $x,y,z∈C$,

$lim sup t → 0 + f ( t z + ( 1 − t ) x , y ) ≤f(x,y);$

(A4) for each $x∈C$, $f(x,⋅)$ is convex and lower semi-continuous.

The following lemma appears implicitly in .

Lemma 2.3 ()

Let C be a nonempty closed convex subset of H, let f be a bifunction of $C×C$ into satisfying (A1)-(A4), and let $r>0$ and $x∈H$. Then there exists $z∈C$ such that

$f(z,y)+ 1 r 〈y−z,Jz−Jx〉≥0,∀y∈C.$

The following lemma was also given in .

Lemma 2.4 ()

Assume that $f:C×C→R$ satisfies (A1)-(A4). For $r>0$ and $x∈H$, define a mapping $T r :X→C$ as follows:

$T r (x)= { z ∈ C : f ( z , y ) + 1 r 〈 y − z , J z − J x 〉 ≥ 0 , ∀ y ∈ C }$

for all $z∈H$. Then the following hold:

1. (1)

$T r$ is single-valued;

2. (2)

$T r$ is firmly nonexpansive, i.e.,

$∥ T r x − T r y ∥ 2 ≤〈 T r x− T r y,x−y〉,∀x,y∈H;$
3. (3)

$F( T r )=EP(f)$;

4. (4)

$EP(f)$ is closed and convex.

Lemma 2.5 ()

Let C be a nonempty closed convex subset of H, let $f:C×C→R$ be a functional, satisfying (A1)-(A4), and let $r>0$. Then, for $x∈H$ and $q∈F( T r )$,

$∥ q − T r x ∥ 2 + ∥ T r x − x ∥ 2 ≤ ∥ q − x ∥ 2 .$

## 3 Strong convergence theorem of modified Mann iteration based on hybrid method

Inspired by Kim and Xu’s results (see ), Mann-type iteration (1.3) is modified to obtain the strong convergence theorem as follows.

Theorem 3.1 Let C be a nonempty bounded closed convex subset of a real Hilbert space H and let $T:C→C$ be an asymptotically nonexpansive mapping with $k n$, denote $L n = 1 n + 1 ∑ j = 0 n k j$. Assume that ${ α n } n = 0 ∞$ is a sequence in $(0,1)$ such that $α n ≤a$ for all n and for some $0. Define a sequence ${ x n } n = 0 ∞$ in C by the following algorithm:

${ x 0 ∈ C is arbitrary , y n = α n x n + ( 1 − α n ) 1 n + 1 ∑ j = 0 n T j x n , C n = { z ∈ C : ∥ y n − z ∥ 2 ≤ ∥ x n − z ∥ 2 + θ n } , Q n = { z ∈ C : 〈 x n − z , x 0 − x n 〉 ≥ 0 } , x n + 1 = P C n ∩ Q n ( x 0 ) , n = 0 , 1 , 2 … ,$
(3.1)

where

Then ${ x n }$ converges strongly to $P F ( T ) ( x 0 )$.

Proof First note that T has a fixed point in C (see ); that is, $F(T)$ is nonempty. We divide the proof of this theorem into four steps as below.

Step 1. We show that $C n$ and $Q n$ are closed and convex for each $n∈N∪{0}$.

From the definition of $C n$ and $Q n$, it is obvious that $C n$ is closed and $Q n$ is closed and convex for each $n∈N∪{0}$. We prove that $C n$ is convex. Since $∥ y n − z ∥ 2 ≤ ∥ x n − z ∥ 2 + θ n$ is equivalent to

$2〈 x n − y n ,z〉≤ ∥ x n ∥ 2 − ∥ y n ∥ 2 + θ n ,$

it follows that $C n$ is convex.

Step 2. We show that $F(T)⊂ C n$, $∀n∈N∪{0}$.

Let $p∈F(T)$ and $n∈N∪{0}$. Then from

$∥ y n − p ∥ 2 = ∥ α n x n + ( 1 − α n ) 1 n + 1 ∑ j = 0 n T j x n − p ∥ 2 ≤ α n ∥ x n − p ∥ 2 + ( 1 − α n ) ( 1 n + 1 ∑ j = 0 n ∥ T j x n − p ∥ ) 2 ≤ α n ∥ x n − p ∥ 2 + ( 1 − α n ) ( 1 n + 1 ∑ j = 0 n k j ∥ x n − p ∥ ) 2 ≤ α n ∥ x n − p ∥ 2 + ( 1 − α n ) L n 2 ∥ x n − p ∥ 2 = ∥ x n − p ∥ 2 + ( 1 − α n ) ( L n 2 − 1 ) ∥ x n − p ∥ 2 ≤ ∥ x n − p ∥ 2 + θ n ,$

we have $p∈ C n$. Next, we show that $F(T)⊂ Q n$, $∀n∈N∪{0}$. We prove this by induction. For $n=0$, we have $F(T)⊂C= Q 0$. Suppose that $F(T)⊂ Q n$, then $∅≠F(T)⊂ C n ∩ Q n$ and there exists a unique element $x n + 1 ∈ C n ∩ Q n$ such that $x n + 1 = P C n ∩ Q n ( x 0 )$. Then

$〈 x n + 1 −z, x 0 − x n + 1 〉≥0,∀z∈ C n ∩ Q n .$

In particular,

$〈 x n + 1 −p, x 0 − x n + 1 〉≥0,∀p∈F(T).$

It follows that $F(T)⊂ Q n + 1$ and hence $F(T)⊂ Q n$ for each n. Thus we obtain $F(T)⊂ C n ∩ Q n$, $∀n∈N∪{0}$. This means that ${ x n }$ is well defined.

Step 3. We show that ${ x n }$ is bounded and $lim n → ∞ ∥ x n −T x n ∥=0$.

It follows from the definition of $Q n$ that $x n = P Q n ( x 0 )$. Therefore

Let $z∈F(T)⊂ Q n$ for all $n∈N∪{0}$. Then

On the other hand, from $x n + 1 = P C n ∩ Q n ( x 0 )∈ Q n$, we have

Therefore, the sequence ${∥ x n − x 0 ∥}$ is nondecreasing. Since C is bounded, we obtain that $lim n → ∞ ∥ x n − x 0 ∥$ exists. This implies that ${ x n }$ is bounded. Noticing again that $x n + 1 = P C n ∩ Q n ( x 0 )∈ Q n$ and $x n = P Q n ( x 0 )$, we have $〈 x n + 1 − x n , x n − x 0 〉≥0$. It follows from (2.1) that

$∥ x n + 1 − x n ∥ 2 = ∥ ( x n + 1 − x 0 ) − ( x n − x 0 ) ∥ 2 = ∥ x n + 1 − x 0 ∥ 2 − ∥ x n − x 0 ∥ 2 − 2 〈 x n + 1 − x n , x n − x 0 〉 ≤ ∥ x n + 1 − x 0 ∥ 2 − ∥ x n − x 0 ∥ 2$

for all $n∈N∪{0}$. This implies that

$lim n → ∞ ∥ x n + 1 − x n ∥=0.$

Since $x n + 1 = P C n ∩ Q n ∈ C n$, we have $∥ y n − x n + 1 ∥ 2 ≤ ∥ x n − x n + 1 ∥ 2 + θ n$. Noticing that $lim n → ∞ k n =1$, then $L n = 1 n + 1 ∑ j = 0 n k j →1$ as $n→∞$. Hence

$∥ y n − x n + 1 ∥≤∥ x n − x n + 1 ∥+ θ n →0.$

Let $A n = 1 n + 1 ∑ j = 0 n T j$. Also since $α n ≤a<1$ for all n, then

$∥ x n − A n x n ∥ = 1 1 − α n ∥ y n − x n ∥ ≤ 1 1 − a ( ∥ y n − x n + 1 ∥ + ∥ x n − x n + 1 ∥ ) → 0 .$

From Lemma 2.2, we have

$lim sup l → ∞ lim sup n → ∞ ∥ A n x n − T l ( A n x n ) ∥ ≤ lim sup l → ∞ lim sup n → ∞ sup x ∈ C ∥ A n x − T l ( A n x ) ∥ =0.$

Therefore,

$lim sup l → ∞ lim sup n → ∞ ∥ A n x n − T l ( A n x n ) ∥ =0.$

Put $k ∞ =sup{ k n :n≥1}<∞$, then

$∥ x n − T l x n ∥ ≤ ∥ x n − A n x n ∥ + ∥ A n x n − T l ( A n x n ) ∥ + ∥ T l ( A n x n ) − T l x n ∥ ≤ ∥ x n − A n x n ∥ + ∥ A n x n − T l ( A n x n ) ∥ + k l ∥ x n − A n x n ∥ ≤ ( 1 + k ∞ ) ∥ x n − A n x n ∥ + ∥ A n x n − T l ( A n x n ) ∥ → 0$

as $n,l→∞$. Thus, we have

$∥ T x n − x n ∥ ≤ ∥ T x n − T l + 1 x n ∥ + ∥ T l + 1 x n − T l + 1 x n + 1 ∥ + ∥ T l + 1 x n + 1 − x n + 1 ∥ + ∥ x n + 1 − x n ∥ ≤ k ∞ ∥ x n − T l x n ∥ + ∥ x n + 1 + T l x n + 1 ∥ + ( k ∞ + 1 ) ∥ x n + 1 − x n ∥ → 0 .$

Step 4. We show that ${ x n }$ converges strongly to $P F ( T ) ( x 0 )$.

Put $w= P F ( T ) ( x 0 )$. Since ${ x n }$ is bounded, let ${ x n k }$ be a subsequence of ${ x n }$ such that $x n k ⇀ w ′$. By Lemma 2.1, we get $w ′ ∈F(T)$. Since $x n = P Q n ( x 0 )$ and $w∈F(T)⊂ Q n$, we have $∥ x n − x 0 ∥≤∥w− x 0 ∥$. It follows from $w= P F ( T ) ( x 0 )$ and the weak lower semicontinuity of the norm that

$∥w− x 0 ∥≤ ∥ w ′ − x 0 ∥ ≤ lim inf k → ∞ ∥ x n k − x 0 ∥≤ lim sup k → ∞ ∥ x n k − x 0 ∥≤∥w− x 0 ∥.$

Thus, we obtain that $lim k → ∞ ∥ x n k − x 0 ∥=∥ w ′ − x 0 ∥=∥w− x 0 ∥$. Using the Kadec-Klee property of H, we get $lim k → ∞ x n k = w ′ =w$. Since ${ x n k }$ is an arbitrary subsequence of ${ x n }$, we can conclude that ${ x n }$ converges strongly to $P F ( T ) ( x 0 )$. □

Remark 3.2 It is not difficult to see from the proof above that the boundedness of C can be discarded if T is a nonexpansive mapping.

## 4 Strong convergence theorem for equilibrium problems

In this section, we prove a strong convergence theorem for finding a common element of the set of zero points of an asymptotically nonexpansive mapping T and the set of solutions of an equilibrium problem in a Hilbert space.

Theorem 4.1 Let H be a real Hilbert space, and let C be a nonempty bounded closed convex subset of H, let $f:C×C→R$ be a functional, satisfying (A1)-(A4). Let $T:C→C$ be an asymptotically nonexpansive mapping with $k n$, denote $L n = 1 n + 1 ∑ j = 0 n k j$ such that $F(T)∩EP(f)≠∅$. Let ${ x n }$ be a sequence generated by

(4.1)

where

$θ n =(1− α n ) ( L n 2 − 1 ) ( diam C ) 2 →0,n→∞.$

Suppose that ${ α n }⊂[0,1]$ and there exists $a∈(0,1)$ such that $α n ≤a$, $∀n∈N$, and ${ r n }⊂(0,∞)$ such that $lim inf n → ∞ r n >0$. Then ${ x n }$ converges strongly to $P F ( T ) ∩ EP ( f ) ( x 0 )$.

Proof We divide the proof of this theorem into four steps as below.

Step 1. Similar to the proof of Step 1 in Theorem 3.1, it is easy to see that $C n$ and $Q n$ are closed convex sets for each $n∈N∪{0}$.

Step 2. We show that $F(T)∩EP(f)⊂ C n ∩ Q n$, $∀n∈N∪{0}$.

Let $p∈F(T)∩EP(f)$. Putting $u n = T r n y n$, $∀n∈N∪{0}$, by (2) of Lemma 2.4, we have $T r n$ is relatively nonexpansive. Noticing that relatively nonexpansive mappings are nonexpansive in Hilbert spaces, then for any $n∈N∪{0}$,

$∥ u n − p ∥ 2 = ∥ T r n y n − p ∥ 2 = ∥ T r n y n − T r n p ∥ 2 ≤ ∥ y n − p ∥ 2 .$

From the proof of Step 2 in Theorem 3.1, we have $∥ u n − p ∥ 2 ≤ ∥ x n − p ∥ 2 + θ n$. Thus $p∈ C n$, hence $F(T)∩EP(f)⊂ C n$. Similar to the proof of Step 2 in Theorem 3.1, it is easy to see that $F(T)∩EP(f)⊂ Q n$. Therefore we have $F(T)∩EP(f)⊂ C n ∩ Q n$, $∀n∈N∪{0}$. This means that ${ x n }$ is well defined.

Step 3. We show that ${ x n }$ is bounded and $lim n → ∞ ∥ x n −T x n ∥=0$.

Similar to the proof of Step 3 in Theorem 3.1, we may obtain that ${ x n }$ is bounded and

$lim n → ∞ ∥ x n + 1 − x n ∥=0.$
(4.2)

Since $x n + 1 = P C n ∩ Q n ∈ C n$, then $∥ u n − x n + 1 ∥ 2 ≤ ∥ x n − x n + 1 ∥ 2 + θ n$. Noticing that $θ n →0$, we have

$∥ u n − x n + 1 ∥≤∥ x n − x n + 1 ∥+ θ n →0.$

Hence

$lim n → ∞ ∥ x n − u n ∥≤ lim n → ∞ ∥ x n − x n + 1 ∥+ lim n → ∞ ∥ x n + 1 − u n ∥→0.$
(4.3)

For $p∈F(T)∩EP(f)⊂ C n$, we have

$∥ u n − p ∥ 2 ≤ ∥ x n − p ∥ 2 + θ n .$
(4.4)

Since $u n = T r n y n$, by (4.4) and Lemma 2.5, we get that

$∥ u n − y n ∥ 2 = ∥ T r n y n − y n ∥ 2 ≤ ∥ y n − p ∥ 2 − ∥ T r n y n − p ∥ 2 ≤ ∥ x n − p ∥ 2 + θ n − ∥ u n − p ∥ 2 → 0 .$
(4.5)

Let $A n = 1 n + 1 ∑ j = 0 n T j$. Since $α n ≤a<1$, $∀n∈N$, then by (4.3) and (4.5), we have

$∥ x n − A n x n ∥ = 1 1 − α n ∥ y n − x n ∥ ≤ 1 1 − a ( ∥ y n − u n ∥ + ∥ u n − x n ∥ ) → 0 .$
(4.6)

From Lemma 2.2, it follows that

$lim sup l → ∞ lim sup n → ∞ ∥ A n x n − T l ( A n x n ) ∥ ≤ lim sup l → ∞ lim sup n → ∞ sup x ∈ C ∥ A n x − T l ( A n x ) ∥ =0.$

Therefore

$lim sup l → ∞ lim sup n → ∞ ∥ A n x n − T l ( A n x n ) ∥ =0.$
(4.7)

Put $k ∞ =sup{ k n :n≥1}<∞$, then

$∥ y n − T l x n ∥ = ∥ α n x n + ( 1 − α n ) A n x n − T l x n ∥ ≤ α n ∥ x n − A n x n ∥ + ∥ A n x n − T l ( A n x n ) ∥ + ∥ T l ( A n x n ) − T l x n ∥ ≤ α n ∥ x n − A n x n ∥ + ∥ A n x n − T l ( A n x n ) ∥ + k l ∥ x n − A n x n ∥ ≤ ( 1 + k ∞ ) ∥ x n − A n x n ∥ + ∥ A n x n − T l ( A n x n ) ∥ .$

Let $n,l→∞$, we get that $∥ y n − T l x n ∥→0$. Thus, by (4.3) and (4.5), we have

$∥ x n − T l x n ∥ ≤∥ x n − u n ∥+∥ u n − y n ∥+ ∥ y n − T l x n ∥ →0.$
(4.8)

Therefore, by (4.8) and (4.2), we obtain that

$∥ T x n − x n ∥ ≤ ∥ T x n − T l + 1 x n ∥ + ∥ T l + 1 x n − T l + 1 x n + 1 ∥ + ∥ T l + 1 x n + 1 − x n + 1 ∥ + ∥ x n + 1 − x n ∥ ≤ k ∞ ∥ x n − T l x n ∥ + ( k ∞ + 1 ) ∥ x n + 1 − x n ∥ + ∥ T l + 1 x n + 1 − x n + 1 ∥ → 0 .$

Step 4. We show that ${ x n }$ converges strongly to $P F ( T ) ∩ EP ( f ) ( x 0 )$.

Since ${ x n }$ is bounded, there exists a subsequence ${ x n k }$ of ${ x n }$ such that $x n k ⇀ w ′$. By Lemma 2.1, we have $w ′ ∈F(T)$. Next we show $w ′ ∈EP(f)$.

From (4.3) and (4.5), we get that $u n k ⇀ w ′$, $y n k ⇀ w ′$. Since $u n = T r n y n$, then

$f( u n ,y)+ 1 r n 〈y− u n , u n − y n 〉≥0,∀y∈C.$

Replacing n by $n k$, we have from Condition (A2) that

$1 r n k 〈y− u n k , u n k − y n k 〉≥−f( u n k ,y)≥f(y, u n k ),∀y∈C.$

Let $k→∞$, since $lim inf n → ∞ r n >0$, by (4.5) and Condition (A4), we get that

$f ( y , w ′ ) ≤0,∀y∈C.$

For $t∈(0,1)$, $y∈C$, let $y t =ty+(1−t) w ′$, then $y t ∈C$, thus $f( y t , w ′ )≤0$. By Condition (A1), we get that

$0=f( y t , y t )≤tf( y t ,y)+(1−t)f ( y t , w ′ ) ≤tf( y t ,y).$

Dividing by t, we have

$f( y t ,y)≥0,∀y∈C.$

Let $t→0$. From Condition (A3), we obtain that $f( w ′ ,y)≥0$, $∀y∈C$. Therefore, $w ′ ∈EP(f)$.

Denote $w= P F ( T ) ∩ EP ( f ) ( x 0 )$. Since $x n + 1 = P C n ∩ Q n ( x 0 )$, $w∈F(T)∩EP(f)⊂ C n ∩ Q n$, then $∥ x n + 1 − x 0 ∥≤∥w− x 0 ∥$. Since the norm is weakly lower semicontinuous, we have

$∥w− x 0 ∥≤ ∥ w ′ − x 0 ∥ ≤ lim inf k → ∞ ∥ x n k − x 0 ∥≤ lim sup k → ∞ ∥ x n k − x 0 ∥≤∥w− x 0 ∥.$

Hence $lim k → ∞ ∥ x n k − x 0 ∥=∥ w ′ − x 0 ∥=∥w− x 0 ∥$. Using the Kadec-Klee property of H, we get $lim k → ∞ x n k = w ′ =w$. Since ${ x n k }$ is an arbitrary subsequence of ${ x n }$, we can conclude that ${ x n }$ converges strongly to $P F ( T ) ∩ EP ( f ) ( x 0 )$. □

## References

1. 1.

Goebel K, Kirk WA: A fixed point theorem for asymptotically nonexpansive mappings. Proc. Am. Math. Soc. 1972, 35: 171–174. 10.1090/S0002-9939-1972-0298500-3

2. 2.

Mann WR: Mean value methods in iteration. Proc. Am. Math. Soc. 1953, 4: 506–510. 10.1090/S0002-9939-1953-0054846-3

3. 3.

Genel A, Lindenstrass L: An example concerning fixed points. Isr. J. Math. 1975, 22: 81–86. 10.1007/BF02757276

4. 4.

Nakajo K, Takahashi W: Strong convergence theorems for nonexpansive mappings and nonexpansive semigroups. J. Math. Anal. Appl. 2003, 279: 372–379. 10.1016/S0022-247X(02)00458-4

5. 5.

Kim TH, Xu HK: Strong convergence of modified Mann iterations for asymptotically nonexpansive mappings and semigroups. Nonlinear Anal. 2006, 64: 1140–1152. 10.1016/j.na.2005.05.059

6. 6.

Yanes CM, Xu HK: Strong convergence of the CQ method for fixed point iteration processes. Nonlinear Anal. 2006, 64: 2400–2411. 10.1016/j.na.2005.08.018

7. 7.

Nilsrakoo W, Seajung S: Weak and strong convergence theorems for countable Lipschitzian mappings and its applications. Nonlinear Anal. 2008, 69: 2695–2708. 10.1016/j.na.2007.08.044

8. 8.

Baillon JB: Un théorème de type ergodique pour les contractions nonlinéairs dans un espaces de Hilbert. C. R. Acad. Sci. Paris Sér. A-B 1975, 280: 1511–1541.

9. 9.

Shimizu T, Takahashi W: Strong convergence theorem for asymptotically nonexpansive mappings. Nonlinear Anal. 1996, 26: 265–272. 10.1016/0362-546X(94)00278-P

10. 10.

Li J: The generalized projection operator on reflexive Banach spaces and its applications. J. Math. Anal. Appl. 2005, 306: 55–71. 10.1016/j.jmaa.2004.11.007

11. 11.

Li J, Lin SL, Zhang CJ: On the existence of Nash equilibriums for infinite matrix games. Nonlinear Anal. 2009, 10: 42–53.

12. 12.

Xu HK: Inequalities in Banach spaces with applications. Nonlinear Anal. 1991, 16: 1127–1138. 10.1016/0362-546X(91)90200-K

13. 13.

Qin X, Su Y: Strong convergence theorems for relatively nonexpansive mappings in a Banach space. Nonlinear Anal. 2007, 67: 1958–1965. 10.1016/j.na.2006.08.021

14. 14.

Wlodarczyk K, Klim D: Equilibria and fixed points of set-valued maps with nonconvex and noncompact domains and ranges. Nonlinear Anal. 2006, 65: 918–932. 10.1016/j.na.2005.10.006

15. 15.

Chadli O, Chbani Z, Riahi H: Equilibrium problems and noncoercive variational inequalities. Optimization 1999, 49: 1–12.

16. 16.

Ansari QH, Yao JC: An existence results for the generalized vector equilibrium problem. Appl. Math. Lett. 1999, 12: 53–56.

17. 17.

Lan H: Common fixed-point iterative processes with errors for generalized asymptotically quasi-nonexpansive mappings. Comput. Math. Appl. 2006, 52: 1403–1412. 10.1016/j.camwa.2006.09.001

18. 18.

Zhao J, He S: A hybrid iteration scheme for equilibrium problems and common fixed point problems of generalized quasi- ϕ -asymptotically nonexpansive mappings in Banach spaces. Fixed Point Theory Appl. 2012., 2012: Article ID 33

19. 19.

Chang S, Wang L, Tang YK: Strong convergence theorems of nonlinear operator equations for countable family of multivalued total quasi- ϕ -asymptotically nonexpansive mappings with applications. Fixed Point Theory Appl. 2012., 2012: Article ID 69

20. 20.

Zegeye H, Shahzad N: Strong convergence theorems for variational inequality problems and quasi- ϕ -asymptotically nonexpansive mappings. J. Glob. Optim. 2012, 54: 101–116. 10.1007/s10898-011-9744-8

21. 21.

Blum E, Oettli W: From optimization and variational inequalities to equilibrium problems. Math. Program. 1994, 63: 123–145.

22. 22.

Combettes PL, Hirstoaga SA: Equilibrium programming in Hilbert spaces. J. Nonlinear Convex Anal. 2005, 6: 117–136.

23. 23.

Takahashi S, Takahashi W: Viscosity approximation methods for equilibrium problems and fixed point in Hilbert space. J. Math. Anal. Appl. 2007, 331: 506–515. 10.1016/j.jmaa.2006.08.036

24. 24.

Jitpeera T, Katchang P, Kumam P: A viscosity of Cesàro mean approximation methods for a mixed equilibrium, variational inequalities, and fixed point problems. Fixed Point Theory Appl. 2011., 2011: Article ID 945051

25. 25.

Browder FE: Nonlinear operators and nonlinear equations of evolution in Banach spaces. Proc. Symp. Pure Math. 1976, 18: 78–81.

26. 26.

Takahashi W, Zembayashi K: Strong and weak convergence theorems for equilibrium problems and relatively nonexpansive mappings in Banach spaces. Nonlinear Anal. 2009, 70: 45–57. 10.1016/j.na.2007.11.031

## Acknowledgements

The authors would like to thank the anonymous referee for some suggestions to improve the manuscript. This work was supported by Research Fund for the Doctoral Program of Harbin University of Commerce (13DL002), Scientific Research Project Fund of the Education Department of Heilongjiang Province and Foundation of Heilongjiang Educational Committee (12521070).

## Author information

Correspondence to Jingxin Zhang.

### Competing interests

The authors declare that they have no competing interests.

### Authors’ contributions

The main idea of this paper is proposed by JZ and YC. JZ prepared the manuscript initially and performed all the steps of the proofs in this research. All authors read and approved the final manuscript.

## Rights and permissions

Reprints and Permissions

Zhang, J., Cui, Y. Iterative algorithms based on hybrid method and Cesàro mean of asymptotically nonexpansive mappings for equilibrium problems. Fixed Point Theory Appl 2014, 16 (2014) doi:10.1186/1687-1812-2014-16

• #### DOI

https://doi.org/10.1186/1687-1812-2014-16

### Keywords

• strong convergence theorem
• asymptotically nonexpansive mapping
• hybrid method
• equilibrium problem
• Cesàro means 